Compendium of monetary policy communiques : monetary policy communiques, numbers 1 to 86, (2001-2012) - Central Bank of Nigeria, Monetary Policy Department; Central Bank of Nigeria (Abuja Nigeria : Central Bank of Nigeria, 2013)
This compendium of the monetary policy communiques of the Central Bank of Nigeria provides a perspective of the areas of emphasis and issues of concern to the Monetary Policy Committee of the through the years
oif 04/09/14
Ref
Keywords: Monetary policy; Banks and banking, Central